EFFECTIVENESS OF THE USE OF INFORMATION TECHNOLOGIES IN MOTHER LANGUAGE LESSONS - Qabilova Kamola; Khurramova Madina Abdunazar qizi (Ustozlar uchun, 2025)
Annotation: This article studies the effectiveness of the use of information technologies in mother tongue lessons. The importance of information technologies in the modern educational process, their impact on the methodology of teaching the mother tongue and their role in activating students' learning activities are analyzed. The article considers innovative methods, digital resources used in mother tongue lessons and ways to increase their effectiveness. Based on the results of the research, conclusions and recommendations are developed.